HUBUNGAN KONTROL DIRI DENGAN KECANDUAN INTERNET PADA SISWA SMP NEGERI WIDYA KRAMA DI KABUPATEN GORONTALO - Muhamad Mursyid; Nurhikma Mahmud (Elsia: Jurnal Psikologi Manusia, 2022)
Social media addiction is a psychological disorder characterized by the behavior of accessing social media by spending a lot of time due to a lack of self-control. This study aims to determine the relationship of self-control with internet addiction. The type of research used is quantitative with a correlational design. The total population is 211 students, sampled using the solving formula. Namely, there are 68 students as samples. They were collecting data using questionnaires and data analysis using Rank Spearman with a significance level of 95% (α=0.05). The results showed that 60 students had good self-control with mild internet addiction, 59 students and statistical test results obtained p=0.001 (p<0.05), so it can be concluded that there is a relationship between self-control and internet addiction and the correlation coefficient value is 0.396, it indicates a high relationship between self-control and internet addiction.